Apakah Profitabilitas dan Struktur Modal Mempengaruhi Nilai Perusahaan? Dividen sebagai Variabel Moderasi - Alien Akmalia (Universitas Muhammadiyah Sorong, 2023)
This research aims to examine the effect of profitability and debt on firm value with dividend policy as a moderating variable. The companies that became the research sample were companies engaged in the manufacturing industry sector for five periods, from 2016 to 2020. This research uses a quantitative approach. The sample selection technique used in this study was the purposive sampling technique. Test the hypothesis using multiple linear regression and moderated regression analysis (MRA) using eviews 12. The results showed that profitability significantly positively affects the firm's value. Meanwhile, the capital structure cannot affect the value of the firm. Dividends are not able to moderate the effect of profitability on firm value. Dividends are also incapable of moderating the influence of the capital structure on firm value. Based on the study results, it can be concluded that profitability is a variable that needs to be considered for investors, companies and stakeholders interested in firm value.